2011
DOI: 10.1007/s00425-011-1488-7
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of hydrogen peroxide, calcium, and ethylene in the induction of the alternative pathway in chilling-stressed Arabidopsis callus

Abstract: The roles of ethylene, hydrogen peroxide (H(2)O(2)), and calcium in inducing the capacity of the alternative respiratory pathway (AP) under chilling temperature in Arabidopsis thaliana calli were investigated. Exposure of wild-type (WT) calli, but not the calli of ethylene-insensitive mutants, etr1-3 and ein2-1, to chilling led to a marked increase of the AP capacity and triggered a rapid ethylene emission and H(2)O(2) generation. Increasing ethylene emission by applying 1-aminocyclopropane-1-carboxylic (an et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 62 publications
6
44
2
Order By: Relevance
“…First, we determined ET accumulation in response to low temperature under our growing conditions. In agreement with Wang et al (2012), when Arabidopsis wild-type plants were exposed to 4°C, a rapid increase of ET was detected ( Figure 8A). It is worth noting that the levels of ET attained were similar to those observed in rci1a mutants under control conditions ( Figures 5B and 8A).…”
Section: Rci1a-regulated Accumulation Of Et In Response To Low Tempersupporting
confidence: 67%
See 2 more Smart Citations
“…First, we determined ET accumulation in response to low temperature under our growing conditions. In agreement with Wang et al (2012), when Arabidopsis wild-type plants were exposed to 4°C, a rapid increase of ET was detected ( Figure 8A). It is worth noting that the levels of ET attained were similar to those observed in rci1a mutants under control conditions ( Figures 5B and 8A).…”
Section: Rci1a-regulated Accumulation Of Et In Response To Low Tempersupporting
confidence: 67%
“…Similarly, ET was also described to increase the capacity of rhododendron plants to cold acclimate (Harber and Fuchigami, 1989). Moreover, it has been demonstrated that ET biosynthesis is required for the accumulation of antifreeze proteins in winter rye during cold acclimation (Yu et al, 2001), and ET has been proposed to protect mitochondrial activity in Arabidopsis during cold acclimation (Wang et al, 2012). In contrast with our findings and all previous reports positively associating ET with plant responses to low temperatures (Field, 1981;Kacperska and Kubacka-Zgbalska, 1985;Harber and Fuchigami, 1989;Ciardi et al, 1997;Yu et al, 2001;Wang et al, 2012), Shi et al (2012) described that ET production is reduced by cold treatment and that ET negatively regulates freezing tolerance in Arabidopsis.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…For example, we and others have shown that AP suppressed reactive oxygen species (ROS) accumulation in mitochondria under normal and stress conditions (Maxwell et al 1999;Wang et al 2010a). Supporting this, the observation that a lack of AOX in tobacco leaf mitochondria increased ROS levels was found (Cvetkovska and Vanlerberghe 2012), and our results also indicated that stress-induced increase in AP reduces ROS accumulation in Arabidopsis (Wang et al 2012). Also, the role of AP in optimizing photosynthesis has recently attracted much attention in plants (Dinakar et al 2010;Raghavendra and Padmasree 2003).…”
Section: Introductionsupporting
confidence: 84%
“…It has been reported that AP is involved in responses to abiotic stress, supported by the fact that AP activity and AOX expression could be induced under various stress conditions, such as high light (Dinakar et al 2010), salinity (Wang et al 2010a), low temperature (Wang et al 2012), drought (Bartoli et al 2005), nutrients supply (Escobar et al 2006;Gonzàlez-Meler et al 2001), and CO 2 concentration (Gonzàlez-Meler et al 2009). These results suggest that AP may have a close relationship with photosynthesis under stress conditions.…”
Section: Introductionmentioning
confidence: 98%